Release and fate of As mobilized via bio-oxidation of arsenopyrite in acid mine drainage: Importance of As/Fe/S speciation and As(III) immobilization. (1st September 2022) - Chen, Hong-Rui; Zhang, Duo-Rui; Li, Qian; Nie, Zhen-Yuan; Pakostova, Eva
Highlights: FeAsS bio-oxidation and As fate in AMD and growth medium were studied. Microbial dissolution of FeAsS was faster and [As]aq lower in AMD than in BSM. The high [Fe]aq /[As]aq ratio in AMD assay favored a formation of tooeleite. As(III) was the main soluble As species during FeAsS bio-oxidation. As(III) released from FeAsS in AMD can be efficiently immobilized by red mud. Abstract: Mining activities expose sulfidic minerals including arsenopyrite (FeAsS) to acid mine drainage (AMD). The subsequent release of toxic arsenic (As) can have great negative implications for the environment and human health. This study investigated the evolution of secondary products and As speciation transformations during arsenopyrite bio-oxidation in AMD collected from a polymetallic mine. Immobilization of the As solubilized via arsenopyrite bio-oxidation using red mud (RM) was also studied. The results show that the high ionic strength (concentrations of dissolved Fe 3+, SO4 2−, and Ca 2+ reached values up to 0.75, 3.38, and 0.35 g/L, respectively) and redox potential (up to +621 mV) of AMD (caused primarily by Fe 3+ ) enhanced the dissolution of arsenopyrite. A high [Fe]aq /[As]aq ratio in the AMD favored the precipitation of tooeleite during arsenopyrite bio-oxidation, and the formation of other poorly crystalline products such as schwertmannite and amorphous ferric arsenate also contributed to As immobilization. Bacterial cells served as important nucleation sites for the precipitation of mineral phases. Arsenopyrite completely dissolved after 12 days of bio-oxidation in AMD and the [As]aq (mainly present as As(III)) reached 1.92 g/L, while a greater [As]aq was observed in a basal salts medium (BSM) assay (reaching 3.02 g/L). An RM addition significantly promoted As(III) immobilization, with final [As(III)]aq decreasing to 0.16 and 1.43 g/L in AMD and BSM assays respectively. No oxidation of As(III) was detected during the immobilization process. These findings can help predict As release from arsenopyrite on contact with AMD and, on a broader scale, assist in designing remediation and treatment strategies to mitigate As contamination in mining. Graphical Abstract: Image, graphical abstract